Capillary angioma with findings of Masson’s tumor. - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2009)
Masson's tumor or intravascular vegetant hemangioendothelioma can be a pure isolated lesion or a focal condition in a pre-existing vascular process, for instance an angioma. The clinical features are not specific and thus the diagnosis is histological. The typical histological sign is a papillary neoformation confined to a vascular lumen and consisting of hyperplasic endothelial cells surrounding thin fibrous stalks (2, 3). The papillae can be inflammatory or fibrous. In the former there is an exuberant endothelial growth during the normal organization of a thrombus, whereas in the latter the endothelial growth could be reactive to blood or lymph stasis (1).